Mengenai Etnik Cina di Indonesia: Selayang Pandang - Dede Oetomo (SIASAT, 2017)
While the majority of studies are still being done as an attempt to understand the Chinese as a separate collection, there is a growing trend in which they are studied as part of Indonesian society. In fact, if we don't study them in this way, as Charles Coppel warned, we might be extending segregation by the Dutch. Examples of studies that integrally include Chinese in analysis of Indonesian society, mostly because they play an important role in economics, are the work of Castles, Robison and Rush.. Many works on Indonesia in general also include a section that discusses Chinese people. Studies on national integration or intergroup relations, written by Indonesian scholars, always include studies of Chinese people without making them too prominent. Government-sponsored Javanology projects often include topics about Chinese people in a series of lectures or seminars. Thus, the study of ethnic Chinese in Indonesia is now more certainly a part of Indonesian studies than Chinese studies.